Analysis Of The Existence Of Indigenous Peoples In The Implementation Of Nagari Government In Solok Regency (Case Study: Nagari Cupak, Gunung Talang District) - Ferrya Hamid Loedy; Aldri Frinaldi (Program Pascasarjana Universitas Negeri Makassar, 2022)
This study aims to determine the analysis of the existence of indigenous peoples in the administration of nagari government in Solok Regency and to describe what are the strengths in the analysis of the existence of indigenous peoples in the administration of nagari government in Solok Regency. This research is qualitative in nature using descriptive methods, so this writer will describe what was done in analyzing the existence of indigenous peoples in the administration of nagari government in Solok Regency, the obstacles encountered in realizing the existence of indigenous peoples and efforts to solve them. The results of this study are the State's effort to apply the same principle in village governance arrangements with different forms of government, which is an effort to keep diversity in unity. However, equating the principle of regulation in a communal society such as Nagari with the Village, in the end resulted in problems in the Nagari Government. The combination of adat and public administration in the context of a hybrid system has made Nagari the same as Desa. The enactment of Law number 6 of 2014 concerning Villages which was responded to by Regional Regulation Number 7 of 2018 has strengthened the position of the Nagari Government as a traditional village with another name. Unfortunately, there is still no customary government that is autonomous according to its special rights of origin. The regulation of Traditional Villages with other names is recognized by the state as long as they do not conflict with the principles of Village regulations regulated by law. The Nagari Government Regulation in Regional Regulation Number 7 of 2018 concerning Nagari which strengthens Nagari as a Traditional Village with another name is still a hybrid system. The existence of Nagari which was revived by the government is something that makes the Nagari people have too high expectations that their management will be able to be managed as Nagari used to be thick with traditional values. If the government does not fully provide genuine autonomy, the advice that researchers can give is the separation between traditional villages and administrative villages.